Hotspot Stres Pada Guru Sekolah Dasar: Analisis Faktor-Faktor Pemicu dan Implikasinya Terhadap Kesejahteraan Pendidikan - Dawous, Gilang Gumilang; Satori, Djam’an; Munir, Munir; Suharto, Nugraha (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2024)
Abstract: Stress and burnout among elementary school teachers in Indonesia are critical issues impacting not only the well-being of educators but also the quality of education delivered to students. This study identifies multiple factors contributing to teacher stress, including high workloads, administrative demands, frequent curriculum changes, and socio-economic challenges. The impact of the COVID-19 pandemic further exacerbated these issues by introducing new challenges, such as the sudden transition to remote learning. Using a descriptive quantitative approach, data were collected from 175 elementary school teachers in Garut Regency through a semantic differential scale to measure stress levels. The findings revealed that the curriculum is the primary source of stress for teachers, followed by gender, age, school accreditation, employment status, and the presence of "Sekolah Penggerak" (Movement Schools). Female teachers and those in the 25-35 age range experienced the highest stress levels, particularly in schools with lower accreditation. Additionally, honorary teachers faced significant stress due to job insecurity and insufficient income, highlighting socio-economic disparities within the teaching profession. The study underscores the urgency of addressing systemic issues, including providing robust professional development programs, enhancing teacher support systems, and ensuring equitable policies for all educators. Effective strategies to manage teacher stress must adopt a holistic approach, integrating institutional and individual interventions. By improving teacher well-being, schools can foster a more supportive environment that enhances both educator satisfaction and student learning outcomes. The study's insights contribute to the broader discourse on improving teacher retention and elevating the standards of education in Indonesia. Keywords: Teacher stress, burnout, elementary education, COVID-19 pandemic, curriculum, teacher well-being, Indonesia Abstrak: Stres dan burnout di kalangan guru sekolah dasar di Indonesia merupakan masalah krusial yang memengaruhi kesejahteraan tenaga pendidik sekaligus kualitas pendidikan yang diberikan kepada siswa. Penelitian ini mengidentifikasi berbagai faktor penyebab stres guru, seperti beban kerja yang tinggi, tuntutan administratif, perubahan kurikulum yang sering terjadi, serta tantangan sosial-ekonomi. Pandemi COVID-19 memperburuk situasi dengan menambahkan tantangan baru, seperti peralihan mendadak ke pembelajaran jarak jauh. Melalui pendekatan kuantitatif deskriptif, data dikumpulkan dari 175 guru sekolah dasar di Kabupaten Garut menggunakan skala diferensial semantik untuk mengukur tingkat stres. Hasil penelitian menunjukkan bahwa kurikulum menjadi sumber stres utama bagi guru, diikuti oleh faktor jenis kelamin, usia, akreditasi sekolah, status kepegawaian, dan status sekolah sebagai "Sekolah Penggerak." Guru perempuan dan mereka yang berada dalam rentang usia 25–35 tahun mengalami tingkat stres tertinggi, terutama di sekolah dengan akreditasi rendah. Selain itu, guru honorer menghadapi stres yang signifikan akibat ketidakpastian pekerjaan dan pendapatan yang tidak mencukupi, menyoroti kesenjangan sosial-ekonomi dalam profesi ini. Studi ini menekankan pentingnya mengatasi isu-isu sistemik, termasuk menyediakan program pengembangan profesional yang memadai, memperkuat sistem dukungan bagi guru, serta memastikan kebijakan yang adil bagi seluruh tenaga pendidik. Strategi efektif untuk mengelola stres guru harus mengadopsi pendekatan holistik yang mencakup intervensi institusional dan individual. Dengan meningkatkan kesejahteraan guru, sekolah dapat menciptakan lingkungan kerja yang lebih mendukung, yang pada akhirnya meningkatkan kepuasan pendidik dan hasil belajar siswa. Temuan penelitian ini memberikan kontribusi pada wacana yang lebih luas tentang upaya mempertahankan guru dan meningkatkan standar pendidikan di Indonesia. Kata kunci: Stres guru, burnout, pendidikan dasar, pandemi COVID-19, kurikulum, kesejahteraan guru, Indonesia